2013
DOI: 10.1002/term.1749
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin biomatrix-conjugated platelet-derived growth factor AB accelerates wound healing in severe thermal injury

Abstract: Controlled delivery of growth factors from biodegradable biomatrices could accelerate and improve impaired wound healing. The study aim was to determine whether platelet-derived growth factor AB (PDGF.AB) with a transglutaminase (TG) crosslinking substrate site released from a fibrin biomatrix improves wound healing in severe thermal injury. The binding and release kinetics of TG-PDGF.AB were determined in vitro. Third-degree contact burns (dorsum of Yorkshire pigs) underwent epifascial necrosectomy 24 h post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 51 publications
(66 reference statements)
0
14
0
1
Order By: Relevance
“…Not only is it important for hemostasis but it also acts as a provisional growth matrix for tissue-specific cells [Wong et al, 2003]. Fibrin sealants are used in several surgical applications and have become a versatile scaffold in the field of tissue engineering, augmenting regeneration in a variety of tissues such as bone [Peled et al, 2007;Weinand et al, 2007;Kaipel et al, 2012], skin [Falanga et al, 2007;Mittermayr et al, 2013], and cartilage [Hildner et al, 2009;Hong et al, 2014]. Fibrin is an especially important factor in nerve regeneration: after an injury, nerve stumps leak fibrin plasma exudate into the affected area, forming fibrin cables that enable Schwann cells to migrate towards the distal stump and form bands of Büngner [Williams et al, 1983;Belkas et al, 2004].…”
mentioning
confidence: 99%
“…Not only is it important for hemostasis but it also acts as a provisional growth matrix for tissue-specific cells [Wong et al, 2003]. Fibrin sealants are used in several surgical applications and have become a versatile scaffold in the field of tissue engineering, augmenting regeneration in a variety of tissues such as bone [Peled et al, 2007;Weinand et al, 2007;Kaipel et al, 2012], skin [Falanga et al, 2007;Mittermayr et al, 2013], and cartilage [Hildner et al, 2009;Hong et al, 2014]. Fibrin is an especially important factor in nerve regeneration: after an injury, nerve stumps leak fibrin plasma exudate into the affected area, forming fibrin cables that enable Schwann cells to migrate towards the distal stump and form bands of Büngner [Williams et al, 1983;Belkas et al, 2004].…”
mentioning
confidence: 99%
“…The extracellular matrix, produced by dermal fibroblasts and ASCs, stimulates cellular growth and proliferation [ 11 ]. Further possible developments of this new multilayered model besides working with endothelial cells could be the additional use of proteins like PDGF to stimulate neovascularization [ 24 ] or incorporation of melanocytes for UV-protection [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among those factors, IGF-1, GM-CSF, PDGF-AB, and HGF are known to stimulate keratinocyte proliferation (Shirakata, 2010). Another study also showed that some of these factors like PDGF-AB could favor the formation of a thicker epidermis once combined with a biodegradable matrix in a burn wound model (Mittermayr et al, 2016). Therefore, fibrin matrices containing growth factors are likely to enhance keratinocyte proliferation, which is important for reepithelialization and wound healing.…”
Section: Figurementioning
confidence: 99%